Giant Conjunctival Nevus in a 12-Year-Old Child - Edit Tóth-Molnár; Eszter Vizvári; Ákos Skribek; András Vörös (Case Reports in Ophthalmological Medicine)
We describe a case of a giant conjunctival nevus presented in a 12-year-old girl with suspicious clinicomorphological appearance. The lesion was noticed by the parents at the age of 3 years as a “fleshy spot” on the bulbar conjunctiva. The lesion remained unchanged until approx. 6 months before recent admission. On slit-lamp examination, a large conjunctival lesion with variegate pigmentation and indistinct margins was detected on the superonasal part of the bulbar conjunctiva of the left eye. Intralesional cysts and vessels were detected with AS-OCT examination. Wide excision and cryotherapy to the scleral bed were performed and amniotic membrane graft was used to restore the ocular surface. Histopathological examination revealed compound type conjunctival nevus and disclosed any sign of malignancy. Although giant conjunctival nevus is a rare entity, precise diagnosis and adequate management are very important as it can be confused with malignant melanoma.